2007
DOI: 10.1007/s00415-006-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment in Multiple Sclerosis Therapy (QUASIMS)

Abstract: Interferon beta (IFN beta) preparations are the most frequently prescribed therapies for patients with relapsing multiple sclerosis (MS). Several open-label observational studies report similar efficacy among IFN beta preparations. The Quality Assessment in Multiple Sclerosis Therapy (QUASIMS) study is a large, open-label observational study designed to compare the effectiveness and tolerability of available IFN beta preparations as disease-modifying therapies for relapsing MS across a wide range of clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
“…Several open-label, postmarketing, observational studies have reported similar efficacy for the three different IFNβ preparations [11,12,13,14,15,16,17,18,19], but only a few have compared these DMTs and GA [20,21]. There is only one report in the literature comparing the effects of all four different immunomodulatory therapies on MS disease progression in patients with relapsing-remitting MS (RRMS); however, the study groups were quite imbalanced, and the reported differences in hazard ratios between the DMTs were attributed to selection bias [22].…”
Section: Introductionmentioning
confidence: 99%
“…Our results, derived from a single center with a small cohort size, are consistent with larger, well-controlled phase III clinical trials and observational studies that have shown equal efficacy among beta IFN products17 and GA,25 probably not only in the short term but in long-term treatment as well, particularly with higher benefit in patients with mild disability and shorter course of disorder at the time of IMT initiation. Relapse-rate reduction in the initial 2 years of treatment predicted clinical efficacy in subsequent years.…”
Section: Discussionsupporting
confidence: 87%
“…Head-to-head, open-label studies have compared the efficacy and tolerability of IFN beta products and GA for the treatment of relapsing MS. Results of these studies are conflicting, with most suggesting equivalent clinical effects of IFN beta products17,2125 but some have shown small treatment differences among the agents, such as potential benefit of GA over IFNs26 or SC IFN beta-1a over IM IFN beta-1a in the Evidence of Interferon Dose Response: European North American Comparative Efficacy study18 or potential benefit of SC IFN beta-1b over IM IFN beta-1a in the Independent Comparison of Interferons trial 27. Although the patients in our study were quasi-randomized to different DMAs (patient allocation was decided by medication availability and not by the physician’s decision), they differed in some of the baseline demographics and disease characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of mortality has not been raised in open trials such as QUASIMS (Quality Assessment in Multiple Sclerosis Therapy) [32], assessing the efficacy and safety of various interferon beta preparations. Their survey was discussed in detail by Limmoroth et al [33].…”
Section: 4mentioning
confidence: 99%